ADE590 - Contemporary Printmaking and Technology / Faculty of Education - UiTM, Faculty of Education (Universiti Teknologi MARA (UiTM), 2023)
The objective of this course is to introduce students to the historical and contemporary fine art prints with studio practice in intaglio, relief, screen process, lithography and monotype as well as technical, standpoint. In Introduction to Printmaking, students will be exploring the Elements of Art while working with different methods and techniques of printmaking. Students will be searching for ways to generate creative ideas both by looking at other artists’ work as well as developing a personal vision. While Printmaking students will be focused primarily on developing technical skills in the various methods, students will also work on developing drawing and design skills and will be encouraged to explore printmaking itself in a creative manner. By the end of the course students will be competent in identifying and creating various types of prints and adopting this outcome in their main focus of studio practice.